Where did that catheter go? A case report of Foley catheter placement in bladder diverticulum with point-of-care ultrasound - Donald Pettet, III; Christopher Smilios; Mathew Nelson (JEM Reports)
Background: Ultrasonography is an effective diagnostic tool for acute urinary retention despite the presence of a Foley catheter to ensure proper Foley location and function. However, there are several previously reported cases of misleading positioning of a Foley catheter balloon [1,3,5]. We report, to our knowledge, the first published case of the presence of a Foley catheter balloon inside a bladder diverticulum that seemingly appears as a bladder perforation on point-of-care ultrasound. Case Report: An 82-year-old man presented to the Emergency Department with an indwelling Foley catheter replaced 5 days ago by his urologist in the outpatient setting. The patient presented with reduced urine output from his Foley with blood clots in the collection bag. A point-of-care ultrasound (POCUS) revealed no evidence of hydronephrosis but there was evidence of a distended bladder with the Foley balloon appearing to be outside of the bladder wall with concern for bladder perforation. On computed tomography scan, the presence of two bladder diverticula were identified at the right anterior wall of the bladder. The Foley catheter tip and balloon were found to be insufflated inside one diverticulum without any evidence of perforation and was successfully manipulated to a proper intraluminal position. Emergency physicians should investigate the presence of Foley catheter positioning in evaluating urinary retention using point-of-care ultrasound. Often these presenting patients have chronic indwelling Foley catheters that are obstructed or incorrectly placed. However, this case demonstrates the potential misinterpretation of a bladder perforation by the presence of a bladder diverticulum and hopefully helps guide other providers in a nuanced approach to further workup and troubleshooting if confronted with similar findings.